2014
DOI: 10.1007/s40003-014-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Conservation Technique for Russian Citrus limon

Abstract: In vitro storage conditions of Citrus limon (L.) Burm. cv. Novoafonsky were developed in this study. Three explants were used: nodal regenerants, seedlings, and micrografted plants. The results obtained in present investigation confirmed that slow growth maintenance of lemon microplants on MS medium allows to store micro-grafted plants and seedlings for 8 and 12 months, respectively, without subculturing. It was also noted that low temperature ?10 ± 2°C and light intensity of 1,000 lux maintain seedlings till … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The results of tables (1 and 2) showed a significant effect of the concentration of medium MS salts on the percentage of cultures viability and regeneration ability (shoots multiplication and rooting), these results agreed with what Ahmed et al (2010), Samarina et al (2014) and Sota & Kongjika (2019) who found that the survival % and shoots multiply decreases with increasing conservation time, but it remained survival.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of tables (1 and 2) showed a significant effect of the concentration of medium MS salts on the percentage of cultures viability and regeneration ability (shoots multiplication and rooting), these results agreed with what Ahmed et al (2010), Samarina et al (2014) and Sota & Kongjika (2019) who found that the survival % and shoots multiply decreases with increasing conservation time, but it remained survival.…”
Section: Discussionsupporting
confidence: 88%
“…One of the storage methods is minimal of nutrient medium by reducing the amount of nutrients. This method has been successfully used in storing different vegetatively propagated horticultural plants, such as, Citrus limon (Samarina et al, 2014), Ziziphus jujube Mill (Sota & Kongjika, 2014), and Prunus webbii (Sota & Kongjika, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Deceleration of growth of the culture can be accomplished by lowering of temperature of cultivation (Dale, 1980;Henshaw et al, 1985;Ruredzo& Hanson, 1991;Dorion et al, 1994;HaeBoong et al, 1996;Samarina et al, 2014;Ali et al, 2016), in combination with low illumination or darkness (Mullin and Schlegel, 1976), changes in the concentration of carbonhydrate and mineral composition of the nutrient medium (Ng and Ng, 1991;Samsonova, 1991;Vysotskaya, 1994;Homes et al, 1982;Rubluo and Kartha, 1985;Rolland et al, 2006), a decrease in oxygen in culture vessels (Brindgen and Staby, 1981;Muromtsev et al, 1990;Winthers, 1979;Brindgen and Staby, 1983;Dorion et al, 1994), the induction of osmotic stress (Henshaw et al, 1980;Ng and Ng, 1991;Ruredzo and Hanson, 1991;Tukai et al, 1988;Codaccioni and Vescovi, 1987;Schilde-Renther et al, 1982;Wanas et al, 1986;Pua and Chong, 1985;Rahman et al, 2010;Ciobaniui DOI: http://dx.doi.org/10.22192/ijarbs.2017.04.05.007 andConstantinovici, 2012), the use of retardants (Westcott, 1981;Cathey, 1964;Zadontsev et al, 1973;Chailakhyan, 1967;Kende et al, 1963).…”
Section: Introductionmentioning
confidence: 99%